Prevalence of trichinellosis and cysticercosis in indigenous pigs from ethnic minorities for selected communes in the Central Highlands (Dak Lak) - Unger, Fred; Chau Thi Minh Long; Nguyen Viet Khong (International Livestock Research Institute, 2016)
Traditionally applied free grazing/roaming of pigs is a known risks factor for selected zoonoses such trichinellosis and cysticercosis which have the potential to cause long lasting health problems in affected humans with sporadic complications such as fatal encephalitis. The ban of free grazing in pigs due to recent policy changes may have contributed to a decrease of both zoonoses and consequently making pork from local or wild pigs safer for the consumer. Despite of the ban some farmers might still use free roaming management at least partly for certain age classes of their pigs. Information on the presence of these zoonoses in pigs produced by ethnic groups is lacking or not updated. Therefore, a serological survey was carried out to provide base line information on the presence of cysticercosis and/or trichinellosis in native pigs in selected communes of the Central Highlands as being part of the Cross CRP project “Scoping study to evaluate the potential of integrated indigenous pig systems to improve livelihoods and safe pork consumption for poor ethnic minority smallholders in the Central Highlands of Vietnam”. While the serological sampling was implemented by WASI all laboratory analysis were carried out by NIVR, a research institute with known experience on the diagnosis for both zoonoses in Vietnam. In addition NIVR provided a training on sample collection and storage.